Peran Self-Efficiacy dalam Memediasi Work Life Balance dan Work Motivation Terhadap Employee Engagement di PT PLN Indonesia Power Unit Bisnis Pemeliharaan - Wahyu Ariani, Dina (MES Bogor, 2025)
Limited career development opportunities in the workplace can lead to decreased self-efficacy and employee engagement, thereby affecting overall workforce stability and organizational performance. Therefore, companies need to understand the role of work life balance and work motivation in maintaining employee stability and performance. This study aims to examine the effect of work life balance and work motivation on employee engagement, with self-efficacy serving as a mediating variable among employees of PT PLN Indonesia Power Maintenance Service Unit. A quantitative approach was employed using a survey method, distributing questionnaires to 117 respondents, who are permanent employees at the KS Tubun branch. A saturated sampling technique was used for sample selection. Data were analyzed using Structural Equation Modeling Partial Least Square (SEM-PLS). The results show that self-efficacy plays a full mediating role in the relationship between work life balance and employee engagement. On the other hand, work motivation does not have a significant indirect effect on employee engagement through self-efficacy, but it has a significant direct effect on employee engagement. These findings indicate that employees' confidence in self-efficacy is a key factor in enhancing their engagement with the organization. The study recommends that company management strengthen work life balance programs and create greater opportunities for career development to support sustainable improvements in self-efficacy and employee engagement.